2014
DOI: 10.1101/lm.035600.114
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the unconditioned stimulus in appetitive conditioning of honeybees differentially impacts learning, long-term memory strength, and the underlying protein synthesis

Abstract: This study examines the role of stimulus duration in learning and memory formation of honeybees (Apis mellifera). In classical appetitive conditioning honeybees learn the association between an initially neutral, conditioned stimulus (CS) and the occurrence of a meaningful stimulus, the unconditioned stimulus (US). Thereby the CS becomes a predictor for the US eliciting a conditioned response (CR). Here we study the role of US duration in classical conditioning by examining honeybees conditioned with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
7
1
Order By: Relevance
“…In tactile conditioning, performance of the control groups tended to decline. We conclude that omega-3 deficiency hinders acquisition, but we do not find an effect on early longterm memory retention (58).…”
contrasting
confidence: 91%
“…In tactile conditioning, performance of the control groups tended to decline. We conclude that omega-3 deficiency hinders acquisition, but we do not find an effect on early longterm memory retention (58).…”
contrasting
confidence: 91%
“…Nevertheless, one can speculate about potential mechanisms that facilitated fear conditioning with the noise burst. Mechanisms such as a stronger habituation to the electric shock (Çevik, ; Dycus & Powers, ; Jordan, Todd, Bucci, & Leaton, ), the use of different US‐calibration procedures for shock versus noise burst (Baker, Mercier, Gabel, & Baker, ; Lipp, ; Randich & LoLordo, ), different US durations (Gallistel & Gibbon, ; Lipp, ; Marter et al, ), different levels of belongingness (Hamm et al, ), and the involvement of different neural pathways (LeDoux, ) may have contributed to better learning in the noise burst versus shock group.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal and human studies have examined the influence of US duration on fear acquisition. Some studies found better conditioning for longer US durations (Ashton, Bitgood, & Moore, ; Bitterman, Reed, & Krauskopf, ; Burkhardt & Ayres, ; Overmier, ), but there are also contradictory results (Frey & Butler, ; Kawai & Imada, ; Marter et al, ; Meiselman & Moore, ; Tait, Kehoe, & Gormezano, ; Wegner & Zeaman, ). Consequently, better conditioning with white noise burst could partially be related to a longer US duration and a longer CS−US overlap.…”
Section: Discussionmentioning
confidence: 99%
“…We used puromycin labeling to assess the effect of Eme on protein synthesis at different periods following injection. This method, which is based on the incorporation of puromycin into nascent peptide chains, has been used to detect changes in protein synthesis levels in various animal models, including mammals, Drosophila, and the honeybee (Schmidt et al, 2009;Marter et al, 2014;Deliu et al, 2017).…”
Section: Eme Induces a Significant Reduction Of Protein Synthesis In The Bee Brainmentioning
confidence: 99%